2017
DOI: 10.4014/jmb.1606.06011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Prototype Foamy Virus Infectivity in Transportin 3 Knockdown Human 293t Cell Line

Abstract: The foamy viruses are currently considered essential for development as vectors for gene delivery. Previous studies demonstrated that prototype foamy virus (PFV) can infect and replicate prevalently in a variety of cell types for its exclusive replication strategy. However, the virus-host interaction, especially PFV-transportin3 (TNPO3), is still poorly understood. In our investigation of the role of TNPO3 in PFV infection, we found lower virus production in TNPO3 knockdown (KD) cells compared with wild-type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Human embryonic kidney 293T (HEK 293T) cells were maintained in Dubecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS, Gibco, USA) and 1% penicillin/ streptomycin (Invitrogen, USA) [22][23][24][25]. The cells were grown in a humidifying incubator at 37 o C with 5% CO…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…Human embryonic kidney 293T (HEK 293T) cells were maintained in Dubecco's Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS, Gibco, USA) and 1% penicillin/ streptomycin (Invitrogen, USA) [22][23][24][25]. The cells were grown in a humidifying incubator at 37 o C with 5% CO…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…Apart from HIV-1 other retroviruses show TRN-SR2 dependency. Faysal Bin et al for example studied the role of TRN-SR2 in the prototype foamy virus (PFV) life cycle [ 42 ]. TRN-SR2 KD cells significantly reduced the infection of PFV (15–20%) compared to the WT cells.…”
Section: Interplay Between Hiv-1 Integrase (In) and Trn-sr2mentioning
confidence: 99%
“…PFV IN possesses a potent nuclear localization signal in its CTD spanning residues 289–371; an amino acid mutation study revealed that some residue positions (308, 313, 318, 324, and 329) notably affect nuclear localization [ 93 ]. TNPO3 is a karyopherin involved in transporting phosphorylated serine/ arginine-rich proteins between the cytoplasm and nucleus, and it is known to be a key factor involved in HIV-1 replication [ 94 , 95 ]. In one study, TNPO3 knockdown reduced PFV production in BHK-21 cells and human 293T cells [ 94 ].…”
Section: Genomic Analysis Of Fv In Dnamentioning
confidence: 99%